Analisis Buku dan Instrumen Buku Kelas IV BAB 1 Sudah Besar Karya Eva Nukman Kurikulum Merdeka Terbitan Kemendikbud 2023 Berdasarkan BSNP - Zidni, Irfan; Purwati, Panca Dewi; Ridha, Wildan Rasya Ar (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to analyze the feasibility of content, language, presentation, and graphics of Indonesian language textbooks for grade IV Chapter 1 entitled “Sudah Besar” by Eva Nukman, based on the standards set by the National Education Standards Agency (BSNP). The analysis method used is descriptive qualitative with an evaluative approach. The results of the analysis show that the material in Chapter 1 is in accordance with the learning outcomes of Phase B of the Merdeka Curriculum, especially in the development of understanding and production of narrative text. Linguistically, the use of spelling is quite appropriate and communicative, although there are some inconsistencies in the use of punctuation and list writing format. In terms of presentation, this book contains learning activities that are contextualized and able to increase students' learning motivation through reflective activities, discussions, and creative projects. Visualization in the book supports optimal understanding of the content. However, there are still shortcomings in the aspects of syntax, morphology, and discourse transition that need to be improved. Overall, the book can be used with little improvement/development to support the learning process of Indonesian language at the elementary school level.